2019
DOI: 10.18502/ijnl.v17i3.375
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism among patients with glioblastoma multiforme

Abstract: Background: Patients with glioblastoma multiforme (GBM) are prone to various metabolic changes such as hypothyroidism. The present study was planned to assess the frequency of hypothyroidism in these patients. Methods: Fifty-two patients with GBM were included. All of them had been treated by tumor resection followed by cranial irradiation. Thyroid function was assessed by measurement of serum thyroid stimulating hormone (TSH), free thyroxin (FT4), and free triiodothyronine (FT3). Results: There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For example, a cohort study ( Berghoff et al, 2020 ) identified a beneficial role of this clinical condition in overall survival in patients with brain metastases, almost doubling life expectancy from the diagnosis of primary and metastatic cancer. Furthermore, the results of a clinical survey showed that almost 40% of patients with brain tumors evaluated had overt or subclinical hypothyroidism and 31% required hormone replacement ( Faghih-Jouybari et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a cohort study ( Berghoff et al, 2020 ) identified a beneficial role of this clinical condition in overall survival in patients with brain metastases, almost doubling life expectancy from the diagnosis of primary and metastatic cancer. Furthermore, the results of a clinical survey showed that almost 40% of patients with brain tumors evaluated had overt or subclinical hypothyroidism and 31% required hormone replacement ( Faghih-Jouybari et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%